Engineering exports of developing countries - Frank Wolter (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1975)
Throughout the sixties and early seventies industrialization efforts made considerable headway in many developing countries (LDCs). In most LDCs the share both of manufacturing value added in GDP and of manufacturing employment in total employment increased within the last fifteen years 5 in contributing to LDCs growth and job creation, manufacturing has kept a prominent place. The industrialization successes were also reflected in the manufactured export flow from LDCs into the world market; its expansion rate surpassed that of developed market economies' (MDCs) manufactured exports. Thus, despite a decline of their overall export share, the LDCs' share in world manufacturing exports rose from 6.4 p.c. in 1960 to 7.9 p.c. in 1970. Inspite of the extensive and sophisticated protective systems which MDCs have partly uphelt to shelter their domestic industries, suppliers from LDCs proved capable of penetrating high-income markets for commodities in the production of which they could benefit from their competitive edge, namely their abundance of cheap labour and raw materials. Export success, however, was not confined to low-skilled labour-intensive or raw-material intensive products; certain LDCs even managed to successfully compete on markets for more sophisticated products. Correspondingly, the classical division of labour between MDCs having the role of factories and LDCs having the role of bread-baskets is slowly but steadily changing.
Keywords: 330